Stigma pada Orang dengan Skizoprenia: Penelitian Pengembangan Media Promosi Kesehatan bagi Keluarga dan Masyarakat - Helfi Agustin; Nur Syarianingsih Syam (Jurnal Kesehatan Komunitas, 2021)
People with Schizophrenia (ODS) often get the stigma of being crazy, even from family and neighbors. In fact, family and community support is needed for ODS to prevent relapse. This study aims to design health promotion media for the ODS family and community. Research and Development level 3 uses the theory of Borg and Gall. Starting with information gathering, planning, initial product development, and initial field testing. Information gathering for product planning was carried out by in-depth interviews with ODS and families, literature studies, discussions with community mental nursing experts. The results of the collection of information were analyzed and it was concluded that there was a need for developing educational videos to eliminate the stigma of â€œcrazy peopleâ€ in ODS. In the planning and product development stage, the video material developed was education on schizophrenia, not a disgrace, support from family and the environment for ODS. After the video is produced, the video is tested for validation. In the initial testing phase, the aspects of the feasibility of the content, the use of language and the presentation of the video material were assessed. The evaluation of the video development material was carried out by assessing the aspects of the media content; media material and practicality. The results of the measurement of the content feasibility aspect are in the good category with an average score of 21.5. The measurement of the language aspect is in the good category with an average score of 20, and the material presentation aspect is in the good category with an average score of 22. The results of the measurement of the media content aspect are in the good category with a score of 26, for the measurement of the aspect of media materials is in the category good with a score of 24, and the practicality aspect of the media is in the good category with a score of 4.Conclusion of the measurement results of the material test and media test are in the good category.